The Inhibitory Factor of Santri Participate Learning Kitab With Sorogan Method During Pandemic Until Post-Pandemic - Umi Latifah (Santri: Journal of Pesantren and Fiqh Sosial, 2022)
Sorogan is one of method learning kitab kuning/ turast which is typical learning in pesantren. Learning that can be called learning directly between Kyai and one by one his students. But Sorogan's method is often the scourge of students to follow it. Similarly, the problem faced Ma'had Jami'ah Mathali'ul Falah. The scourge of the preacher in front of Pak Kyai directly makes students not infrequently avoid and do not follow the activities of learning Kitab, especially during the pandemic and post-pandemic. This paper's writing aims to know what is and how it becomes a factor inhibiting santri following the activities of sorogan Kitab. The dissemination of questionnaires and interviews with santri that was chosen as purposive sampling was then analyzed using mixed methods as a sequential explanatory method. Then completed with an interview with santri that was chosen as purposive sampling. They are chosen from different Pondok to find the reality and show up the variants data from different places. The results showed a lack of knowledge about Arabic language tools, previous education background, lack of time, lack of enthusiasm from themselves also became an obstacle to the participation of santri following the sorogan and for a long reason they haven’t finished their sorogan yet. The pandemic does not significantly affect learning sorogan in pesantren, and still going on with health protocols. In fact, santri really enjoys learning because they want to know the contents/meanings contained that are very important a provision for life.